How big is circular economy potential on Caribbean islands considering e-waste?. (1st October 2021) - Mohammadi, Elham; Singh, Simron Jit; Habib, Komal
Abstract: While excessive use of electronics and the resulting e-waste is a global problem, the situation is even more acute on small islands as bounded systems and the enormous costs associated with shipping it elsewhere. Dumping e-waste on islands can cause pollution of ground and surface water and degradation of coastal and marine resources. Yet, research that supports island governments to deal with their e-waste is scarce. This paper explores the viability of a circular economy (CE) and asks whether this could be a promising solution for islands to tackle their e-waste challenge. In pursuit of this aim, the CE potential of e-waste is analyzed on five Caribbean islands: Aruba, Barbados, Grenada, Jamaica, and Trinidad and Tobago. The resource quantity of e-waste generated between 2020 and 2025 is estimated, and the economic value is assessed for the embedded materials. Using sensitivity analyses, three scenarios of exploitable e-waste and their potential economic values were calculated, considering the recovery of 20%, 50%, or 100% of e-waste stocked on the islands between 2001 and 2019. Expert interviews were conducted to identify existing e-waste management practices, if any. The results reveal that more than 317.4 kt of secondary materials would be available for recovery, comprising a significant amount of base and precious metals, such as aluminum, copper, silver, gold, and palladium. The estimated economic value of these materials is estimated to be more than $546 million. However, according to the sensitivity analysis, if these islands had started the recovery of resources in early 2001, this value would almost triple to $1, 430 million - equivalent to nearly 30% of the total gross domestic product (GDP) from mining and quarrying in the entire Caribbean community, from just these five islands. Due to economies of scale that limit smaller nations, regional co-operations and initiating industrial symbiosis would be essential for desirous islands to shift to a CE. CE can support resource self-sufficiency on islands and bring several social, environmental, and economic benefits. This research is the first to provide an island-specific perspective to help decision-makers manage e-waste flows by including participatory CE implementation methods. Highlights: Circular economy can be a promising solution for islands to tackle their e-waste challenge. A significant quantity of base, rare and precious metals are available for recovery from e-waste in the Caribbean. Achieving a circular economy would diversify the economy, create new jobs, improve human and ecosystem health. Circular economy of e-waste can enhance resource security and self-sufficiency on islands. Establishing regional collaborative alliances is essential for an effective e-waste management system.